Biology and Management of Galinsoga (Galinsoga quadriradiata) in Ornamental Crop Production - Thomas Patrick Smith; Chris Marble; Shawn Steed; Nathan Boyd (EDIS)
Galinsoga (Galinsoga quadriradiata) is an erect (upright), herbaceous, short-lived warm-season annual weed in Florida landscapes, container nurseries, and other agricultural production systems. In nurseries and landscapes, galinsoga can be a troublesome weed, but it has been utilized by some cultures for food or medicinal purposes. This new 5-page article is written for green-industry professionals and others to aid in the identification and management of galinsoga in and around ornamental plants. Written by Thomas Smith, Chris Marble, Shawn Steed, and Nathan Boyd, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep593